Designing a Wall Paint Mixing Machine Using Suspension - Saputro, Wisnu; Robbani, Ilham; Diwantara, Muhammad; Apriyana, Eko (JURNAL TEKNIK INDUSTRI, 2023)
Paint is a type of color that is quite familiar in our country, Indonesia, paint in the form of a liquid that serves to protect, strengthen and beautify, in addition to affordable prices, the quality is also the best choice for today. The demand for paint needs that are still large in Indonesia encourages the paint machine assembly industry to always try to present types of colors according to the needs of workers or building shop entrepreneurs. And to be able to meet the needs of consumers many color choices. In the production section of the paint machine assembly industry made from safety for workers or operators. The technology of the painting machine has also used an LCD computer along with the package so that it can make it easier for workers. This technology is the latest feature technology for now. This technology also has another feature, namely suspension, suspension is a tool to raise and lower the object. The purpose of this research is to design an effective and efficient suspension system paint mixing machine at an affordable price. Based on the results of this study, it produced a simple paint mixer that uses a suspension accompanied by several other additional features so that it can make it easier for workers to use. Keywords: paint machine, automatic, suspension